The Coal and Other Mines (Mechanics and Electricians) Regulations 1965 - Lee, Fred (Her Majesty's Stationery Office, 1965)
STATUTORY INSTRUMENTS 1965 No. 1559 MINES AND QUARRIES The Coal and Other Mines (Mechanics and Electricians) Regulations 1965
ERAF: A6.SI.1965.1559
Keywords: Statutory Instruments; mines; quarries; coal